Conducting polymer based materials for on-skin applications - Fu, Xiaoxu (Nanyang Technological University, 2021)
Skin health is of a major concern especially for construction workers who are exposed to extended sun radiation and thus are more prone to develop pathological skin conditions, such as skin cancer. In this study, a portable, fast and economical skin mapping technique was established, aiming to assist on-site dermatological skin diagnostics with the option of customized treatment of pathological skin conditions. To do that, the electro-controlled deposition of conducting polymers in the presence of the insulating skin stamp was performed on various conducting surfaces. As a result of electropolymerization of conducting polymers onto sebum-conductor surfaces the 3D skin patterns relating to the skin topographies were realized. The 3D skin patterning demonstrated adequate capability for recognition and reproduction of various skin features, supporting a resolution of up to μm-level, which encompass most circumstances in dermatology diagnosis. To achieve portability, the device prototype entirely powered by dry battery was developed. To add the functionality to the developed 3D skin patterning technique, such as wound treatment, cellulose substrates were introduced to improve flexibility and breathability of the material. Cellular studies proved that the developed material is cytocompatible and safe to use in on-skin applications. Furthermore, both PET- and cellulose-based substrates were explored on electro-controlled metal loading and release. Zn2+ and Cu2+ were firstly investigated as therapeutic ions via passive or active methods. The results showed a successful loading and well-controlled release profile within an effective concentration range in ppb level. The study of various conducting polymer based materials shows a promising perspective not only in on-skin diagnosis but also in skin treatment.